The ontological meaning of the metaphor of "cultural trauma" (Journal of Philosophy Culture and Political Science, 2021)
The aim of the article is to reveal the ontological meaning of the metaphor «cultural trauma». Theauthors analyze the essence of the concepts «metaphor», «trauma», «culture» from the point of view ofphilosophical knowledge. The complexity of determining the structural elements of this metaphor isshown. The context of the formation and the conceptual content of Western studies devoted to this issueare considered. The novelty of the research lies in the structuring of scientific knowledge of the «culturaltrauma» metaphor. It is shown that the concept of «trauma» is used in modern Western humanitarianand social studies, as well as in the traditional and modern worldview of the Kazakh society on a mentalbasis. Trauma is defined not only as a mental pathology, but also as an interdisciplinary way or aspiration to understand the truth. It is argued that «trauma» is a concept that brings together individual andcollective ideas, exploring the negative, dysfunctional consequences of social change. Opportunities forthe prospects for the development of similar research practices within the framework of the Kazakh society are offered. The authors, as an example of the proposed perspective, analyze a number of works ofKazakh literature. However, before studying the phenomenon of «cultural trauma» in the Kazakh culturalheritage in the field of humanities and social sciences, it is necessary to substantiate its methodologicalaspectsKey words: culture, trauma, metaphor, cultural trauma, phenomenon, ontology.